Digitalisation, digital transformation – In the practice of the National Tax and Customs Office - Vozár, Anikó; Bán, Erika (Public Finance Quarterly, 2024)
Our research has shown that digital solutions have increased the efficiency of official audits carried out by the National Tax and Customs Administration (hereinafter Nemzeti Adó- és Vámhivatal, NAV), making it easier to compare tax authority and taxpayer data. A new way of thinking has been introduced at the NAV as a result of digitalisation solutions. The overall impact is positive, with synergies between NAV and taxpayers. Following the beginnings, we will look at the digital solutions of the present and map out the opportunities for development in the near future, using several research methods. What has NAV’s digitisation activity given us and what can it give us? Time, efficiency, smoother administration, more queries for taxpayers and their partners. A change of mindset, a changing audit methodology, permanent change. Transforming jobs, the possibility of using artificial intelligence. The focus of audits will remain on the examination of human activities, but the role of the human factor in audits will be reduced.